2006
DOI: 10.1016/j.jpowsour.2006.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Control design of an atmospheric solid oxide fuel cell/gas turbine hybrid system: Variable versus fixed speed gas turbine operation

Abstract: This study is focused on a hybrid fuel cell/gas turbine (FC/GT) system with an atmospheric pressure solid oxide fuel cell (SOFC). The impact of the gas turbine rotational speed on dynamic performance and controllability of a hybrid system is investigated. The transient response of the FC/GT system to perturbations in the power demand has been investigated. Two operational strategies of gas turbines are compared: (1) fixed speed operation, and (2) variable speed operation. For both operation strategies, a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
63
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 10 publications
0
63
0
Order By: Relevance
“…The model is nonlinear based on transport and conservation principles. The modeling methodology used has been verified experimentally and utilized for controls development in previous work [2][3][4][5][6][7][8][9]. Since the focus of the paper is controls, the physical dynamic model is only briefly presented in Appendix A.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model is nonlinear based on transport and conservation principles. The modeling methodology used has been verified experimentally and utilized for controls development in previous work [2][3][4][5][6][7][8][9]. Since the focus of the paper is controls, the physical dynamic model is only briefly presented in Appendix A.…”
Section: Introductionmentioning
confidence: 99%
“…a. Fuel and air temperatures at the entrance to the fuel cell stack should be maintained to within 200 K of the fuel cell operating temperature [6,7,10,14,15]. b. Endothermic cooling caused by fuel reformation reactions at the fuel cell anode inlet should be minimized.…”
Section: Introductionmentioning
confidence: 99%
“…In the SOFC/GT hybrid system, the fuel cell high temperature SOFC exhaust drives a gas turbine, providing air flow and pressurizing the SOFC while driving an electric generator that produces additional electrical power. As a result, SOFC/GT hybrid systems have demonstrated efficiencies above 50% [5,18] and studies have shown the possibility for electrical conversion above 70% [4,19] when operating on natural gas and above 60% in an integrated coal gasification plant [6,19]. Higher efficiency reduces CO 2 emissions while separated fuel and air flows in the SOFC allow system designs for CO 2 sequestration with minimal performance cost [16,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Similar SOFC technology development programs have been rapidly advancing SOFC technology in Europe and Japan [22,23]. At the system design level both prototypes and mathematical modeling have developed multiple system designs and control strategies [8,19,[24][25][26][27]. The current work seeks to illustrate the fidelity of the hybrid system modeling methodology developed at the National Fuel Cell Research Center [10,18,24,28,29] and draw attention to critical system sensitivities caused by fluctuations in temperature, electrochemical current, and fuel composition variations.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, several efforts have been made towards the development and implementation of control strategies for DERs (e.g., [3], [4], [5], [6], [7], [8]). Important contributions in this direction include the use of conventional and model-based feedback control algorithms to regulate various types of grid-connected DERs in order to enhance power system stability (e.g., [9], [10], [11], [12]), mitigate power quality problems (e.g., [13]) and improve the continuity of electricity supply (e.g., [14]), as well as the development of various distributed control and coordination architectures using multi-agent based control approaches (e.g., [15], [16], [17], [18]).…”
mentioning
confidence: 99%